(untitled) (Proceedings of International Educators Conference, 2023)
In our country, great attention is paid to the provision of housing to the population, for this purpose, to the construction of multi-storey buildings that fully meet the requirements of the times. Of course, the construction of low-income housing for families with many children and people with disabilities is not excluded.